2022
DOI: 10.4103/gmit.gmit_92_20
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laparoscopy for Ovarian Tumor Due to Salmonella Infection

Abstract: Ovarian abscess is thought to be caused by ascending infection. We experienced a case with ovarian abscess caused by Salmonella. The patient had been monitored for endometrial cysts at an outpatient clinic. She visited our hospital emergently with chief complaints of persistent fever and diarrhea. Although sexually transmitted disease was not suspected, she was diagnosed with pelvic inflammatory disease due to her high C-reactive protein (CRP) level and started antibacterial treatment. Two days later, diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The pelvic organs are a rare but described extra‐intestinal location of invasive Salmonella infections 5 . In literature, there are more than 30 cases documented of a Salmonella abcedation of the ovaries, mostly occurring in case of a pre‐existing cyst 7,13–15 . A few case studies of pelvic inflammatory disease caused by a non‐typhoid Salmonella species are reported 5,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pelvic organs are a rare but described extra‐intestinal location of invasive Salmonella infections 5 . In literature, there are more than 30 cases documented of a Salmonella abcedation of the ovaries, mostly occurring in case of a pre‐existing cyst 7,13–15 . A few case studies of pelvic inflammatory disease caused by a non‐typhoid Salmonella species are reported 5,16 .…”
Section: Discussionmentioning
confidence: 99%
“… 5 In literature, there are more than 30 cases documented of a Salmonella abcedation of the ovaries, mostly occurring in case of a pre‐existing cyst. 7 , 13 , 14 , 15 A few case studies of pelvic inflammatory disease caused by a non‐typhoid Salmonella species are reported. 5 , 16 Moreover, non‐typhoidal Salmonella infections are described in pregnancy resulting in various complications, including septic abortion, pregnancy loss, chorioamnionitis and neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually a consequence of PID. [ 1 2 3 ] A TOA may form as an untoward consequence of a hysteroscopic procedure. This adverse outcome is rare, with an incidence rate of about only 0.2%.…”
Section: Discussionmentioning
confidence: 99%